Endothelial Dysfunction in Resuscitated Cardiac Arrest (ENDO-RCA): safety and efficacy of low-dose prostacyclin administration and blood pressure target in addition to standard therapy, as compared to standard therapy alone, in post-cardiac arrest syndrome patients: study protocol for a randomized controlled trial. Issue 1 (December 2016) - Meyer, Anna; Ostrowski, Sisse; Kjaergaard, Jesper; Johansson, Pär; Hassager, Christian
Abstract Background Morbidity and mortality following initial survival of cardiac arrest remain high despite great efforts to improve resuscitation techniques and post-resuscitation care, in part due to the ischemia-reperfusion injury secondary to the restoration of the blood circulation. Patients resuscitated from cardiac arrest display evidence of endothelial injury and coagulopathy (hypocoagulability, hyperfibrinolysis), which in associated with poor outcome. Recent randomized controlled trials have revealed that treatment with infusion of prostacyclin reduces endothelial damage after major surgery and AMI. Thus, a study is pertinent to investigate if prostacyclin infusion as a therapeutic intervention reduces endothelial damage without compromising, or even improving, the hemostatic competence in resuscitated cardiac arrest patients. Post-cardiac arrest patients frequently have a need for vasopressor therapy (catecholamines) to achieve the guideline-supported blood pressure goals. To evaluate a possible catecholamine interaction with the primary endpoints of this study, included patients will be randomized into two different blood pressure goals within guideline-recommended targets. Methods/design A randomized, placebo-controlled, double-blind investigator-initiated pilot trial in 40 out-of-hospital-cardiac-arrest (OHCA) patients will be conducted. Patients will be randomly assigned to either the active treatment group (48 hours of active study drug (iloprost, 1 ng/kg/min) or to the control group [placebo (saline) infusion]. Target mean blood pressure levels will be allocated 1:1 to 65 mmHg or approximately 75 mmHg, which gives four different permutations, namely: (i) iloprost/65 mHg, (ii) iloprost/75 mmHg, (iii) placebo/65 mmHg, and (iv) placebo/75 mmHg. All randomized patients will be treated in accordance with state-of-the art therapy including targeted temperature management. The primary endpoint of this study is change in biomarkers indicative of endothelial activation and damage, [soluble thrombomodulin (sTM), sE-selectin, syndecan-1, soluble vascular endothelial growth factor (sVEGF), nucleosomes] and sympathoadrenal over activation (epinephrine/norepinephrine) from baseline to 48 hours post-randomization. The secondary endpoints of this trial will include: (1) the hemostatic profile [change in functional hemostatic blood test (thrombelastography (TEG) and whole blood platelet aggregometry (multiplate)) blood cell and endothelial cell-derived microparticles]; (2) feasibility of blood pressure target intervention (target 90 %); (3) interaction of primary endpoints and blood pressure target; (4) levels of neuron-specific enolase at 48 hours post-inclusion according to blood pressure targets. Discussion The ENDO-RCA study is a pilot study trial that investigates safety and efficacy of low-dose infusion of prostacyclin administration as compared to standard therapy in post-cardiac arrest syndrome patients. Trial registration Trial registration at ClinicalTrials.gov (identifierNCT02685618 ) on 18 February 2016.